Biomechanics of Central Incisor Endocrowns with Different Lengths and Milled Materials after Static and Vertical Loading: A Finite Element Study - Waleed M. S. Alqahtani; Salah A. Yousief; Raafat Tammam; Rami M. Galal; Ali Brakat; Hend Mohamed El Sayed; Ala’a Kamal; Mohammed Noushad; Mohammad Zakaria Nassani (International Journal of Dentistry)
Statement of Problem. The performance of central incisor endocrowns with varying crown heights and different computer-aided designs and computer-aided manufacturing materials is not clear. Purpose. The aim of this study was to compare and assess the stress distribution and failure possibility of endodontically treated central incisor protected with endocrowns with different heights, with various CAD–CAM blocks such as IPS e.max CAD, Katana Zirconia, and Zolid Fx Zirconia. Materials and Methods. A root canal-treated central incisor (plastic model) restored with an endocrown was scanned with a laser scanner to prepare a control model with a CAD software and then transferred to an FEA software. Proposed crown heights were 2, 4, and 6 mm. The model that was duplicated and restored with CAD–CAM blocks, IPS e.max CAD, Katana Zirconia, and Zolid Fx Zirconia were tested as endocrown materials. Bone geometry was simplified to be two coaxial cylinders in all models. Stress distributions under 50 N axial and oblique (with 135° angle from the vertical plane) loading were analyzed. Each model was then subjected to two occlusal loading conditions—the lingual slope of the incisal edge and the junction between incisal and middle thirds. Eighteen runs and calculations were performed to determine the endocrown height and material effect. Results. The results showed a minor or negligible effect of changing the endocrown material. Increasing endocrown height was shown to reduce stresses and deformations on most of the model components (bone, gutta-percha, periodontal ligament, and endocrown), except root and cement. Differences in deformations and stresses between the two models of 4 and 6 mm were relatively smaller (ranged between 1% and 30%) compared to those between the 2 and 4 mm models (ranged between 10% and 400%). Conclusions. The material used to fabricate endocrowns did not show considerable effect on the underlying structures. However, the endocrown design (2, 4, and 6 mm height) was shown to affect all components of the studied systems. Increasing endocrown height is recommended for bone, periodontal ligaments, and endocrown body, as it reduces stresses and deformations. On the other hand, it dramatically increases stresses on the root and cement layer. Smaller endocrown sizes represent an acceptable treatment option when there is a healthy periodontal state, while using larger sizes will be more suitable when there is a periodontal compromise with bone loss.